Simulation studies of the interactions between membrane proteins and detergents. - Bond, P; Cuthbertson, J; Sansom, MS (2005)
Interactions between membrane proteins and detergents are important in biophysical and structural studies and are also biologically relevant in the context of folding and transport. Despite a paucity of high-resolution data on protein-detergent interactions, novel methods and increased computational power enable simulations to provide a means of understanding such interactions in detail. Simulations have been used to compare the effect of lipid or detergent on the structure and dynamics of membrane proteins. Moreover, some of the longest and most complex simulations to date have been used to observe the spontaneous formation of membrane protein-detergent micelles. Common mechanistic steps in the micelle self-assembly process were identified for both alpha-helical and beta-barrel membrane proteins, and a simple kinetic mechanism was proposed. Recently, simplified (i.e. coarse-grained) models have been utilized to follow long timescale transitions in membrane protein-detergent assemblies.